Nivel de Satisfacción de los usuarios del Subcentro Lucha Obrera en la ciudad de Babahoyo. - Chiquito Molina, Jean Carlos (2018)
he present case study that has the name "Level of Satisfaction of the users of the Workers 'Fighting Subcenter in the city of Babahoyo" has been made with the objective of revealing multiple deficiencies that the Workers' Fighting Sub-Center presents when providing attention to the different users that arrive every day looking for timely and efficient care for their ailments. Nowadays, for companies, whether commercial, service or industrial, among others, they look for greater customer satisfaction (user) because it is an indicator that allows them to identify the performance perceived by the client, whether it is the product or service they provide, to achieve maximum customer satisfaction, a committed and highly oriented customer service staff is needed.